Liquorilactobacillus satsumensis from water kefir yields α-glucan polysaccharides with prebiotic and synbiotic qualities. (15th August 2022) - Tan, Li Ling; Ngiam, Jia Jun; Sim, Edric Shao Zhe; Conway, Patricia Lynne; Loo, Say Chye Joachim
Abstract: Exopolysaccharides from water kefir grains are a potential source of novel, food-safe and functional materials. Herein, prebiotic properties of polysaccharides produced by water kefir-derived Liquorilactobacillus satsumensis bacteria were explored. Strains were cultured in sucrose-supplemented media for exopolysaccharides production, and partial hydrolysis was performed to yield shorter chain polysaccharides. Structural characterization revealed that hydrolyzed polysaccharides were branched glucans comprising α-1, 6 bonds and α-1, 3/α-1, 4 branching, with molecular weight of 10 kDa. Hydrolyzed polysaccharides demonstrated selective utilization by probiotics, but not by pathogens, and were non-digestible by human digestive enzymes. Particularly, hydrolyzed polysaccharides were fermentable by kefir-derived probiotics, and these were combined in a novel kefir synbiotic formulation. Using large bowel simulated conditions, it was demonstrated that hydrolyzed polysaccharides and kefir synbiotics promoted Bacteroidetes abundance, and increased acetate, propionate, and butyrate concentrations. Overall, hydrolyzed glucans from Liquorilactobacillus satsumensis have prebiotic properties with enhanced benefits in a synbiotic when combined with kefir probiotics. Graphical abstract: Unlabelled Image